Tempe: Live Scripting For Live Data - DeLIne, Robert; Fisher, Danyel; Chandramouli, Badrish; Goldstein, Jonathan; Barnett, Mike; Terwilliger, James; Wernsing, John (Visual Languages and Human-Centric Computing (VL/HCC), 2015 IEEE Symposium on, 2015)
Data scientists are increasingly working with live streaming data, for example, business telemetry and signals from wearable devices and the Internet of Things. Unfortunately, current tools for exploratory data analysis provide poor support for streaming data. This paper presents Tempe, a data science environment for temporal and streaming data. Tempe's extensible scripting environment allows for live programming, displays interactive, continually updating visualizations, and provides a uniform query language for both stored and live data. We discuss the streaming features of Tempe and evaluate our design choices with a deployment study at Microsoft with a product team who used Tempe continuously for six months.